1996
DOI: 10.1007/bf01629578
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium deficiency: Possible role in osteoporosis associated with gluten-sensitive enteropathy

Abstract: Osteoporosis and magnesium (Mg) deficiency often occur in malabsorption syndromes such as gluten-sensitive enteropathy (GSE). Mg deficiency is known to impair parathyroid hormone (PTH) secretion and action in humans and will result in osteopenia and increased skeletal fragility in animal models. We hypothesize that Mg depletion may contribute to the osteoporosis associated with malabsorption. It was our objective to determine Mg status and bone mass in GSE patients who were clinically asymptomatic and on a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 28 publications
1
58
0
2
Order By: Relevance
“…Two studies have reported an increased bone mass in postmenopausal osteoporosis after Mg therapy [47,57]. Lastly, celiac sprue patients with evidence of intracellular Mg depletion were observed to have a significant increase in bone mineral density during 2 years of Mg replacement therapy [58]. Further investigations is indicated in order to determine the mechanism(s) by which Mg depletion results in abnormal skeletal metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have reported an increased bone mass in postmenopausal osteoporosis after Mg therapy [47,57]. Lastly, celiac sprue patients with evidence of intracellular Mg depletion were observed to have a significant increase in bone mineral density during 2 years of Mg replacement therapy [58]. Further investigations is indicated in order to determine the mechanism(s) by which Mg depletion results in abnormal skeletal metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…However, many other supplements including 500 mg/day Ca were simultaneously used, making it difficult to distinguish the effects of Mg 2ϩ . Subsequently, multiple studies have examined the effect of Mg 2ϩ supplementation in different populations (138,436,494). Mg 2ϩ seems to increase BMD in all of the studies, although the effects are relatively small (1-3%) and the small study sizes limit the conclusions that can be made from them.…”
Section: Osteoporosismentioning
confidence: 99%
“…Hypomagnesemia was associated with lower PTH synthesis and secretion (29)(30)(31) and with altered target organ responsiveness to PTH action (30). Mg supplementation for 2 years significantly increased BMD in patients with osteoporosis associated with gluten-sensitive enteropathy (32).…”
Section: Discussionmentioning
confidence: 99%